1 Clement as an argumentative text - Du Toit, David S.; Cerone, Jacob N.; Hager, Kathrin (Novum Testamentum / Supplements, 2026)
"This volume explores the significance of 1 Clement as an argumentative text - a text that substantiates and offers reasons for a specific course of action which readers of the work should take. The contributions to this volume analyze the various argumentative strategies the author of 1 Clement employs in service of the letter's overall aims. Some essays focus on the cultural knowledge underlying the argumentation, while others on the function and use of Scripture. Several essays offer insights from other disciplines - theories of argumentation, metaphor, and (literary and cultural) space, as well as historical anthropology - to facilitate the analysis of 1 Clement's argument. The final two essays investigate the way the argumentative structure of 1 Clement was interpreted and used in two very different contexts of reception"-- Provided by publisher